Displacement-acceleration control via stiffness-damping collaboration - Takewaki, Izuru (Earthquake engineering & structural dynamics, 1999)
An approach is presented to stiffness–damping simultaneous optimization for displacement–acceleration simultaneous control. To make a shear building model stiffer, the sum of mean‐square interstorey drifts to stationary random excitations is minimized or the mean‐square top‐floor absolute acceleration is maximized subject to the constraints on total storey stiffness capacity and total damper capacity. Optimality conditions are derived and a two‐step optimization method using the optimality conditions is devised. In the first step, the optimal design is found for a specified set of total storey stiffness capacity and total damper capacity. In the second step, a series of optimal designs is found with respect to a varied set of total storey stiffness capacity and total damper capacity. While increase of total stiffness capacity and increase of total damper capacity are both effective in reduction of deformation, only increase of total damper capacity is effective in reduction of acceleration. Acceleration control is carried out in the second step via increase of total damper capacity. It is shown through numerical examples that the proposed method is efficient and reliable. Copyright © 1999 John Wiley & Sons, Ltd.